2019
DOI: 10.3390/molecules24040701
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Design of New Isobaric Labeling Reagents for Quantitative Proteomics

Abstract: Modern mass spectrometry is one of the most frequently used methods of quantitative proteomics, enabling determination of the amount of peptides in a sample. Although mass spectrometry is not inherently a quantitative method due to differences in the ionization efficiency of various analytes, the application of isotope-coded labeling allows relative quantification of proteins and proteins. Over the past decade, a new method for derivatization of tryptic peptides using isobaric labels has been proposed. The lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 72 publications
1
53
0
Order By: Relevance
“…The important features of employed methods and their individual merits have been reviewed extensively in 2012 [22]. Concomitant with analysis techniques, MS data analysis software has matured in the last years [23], now offering robust, label-free quantification and multiplexing of up to 10 samples [24] in one MS run. Since 2012, some of these technological advances have been implemented, yet traditional methods have remained popular in Brucella proteomics.…”
Section: Proteomics Technologies and Their Use For Brucellamentioning
confidence: 99%
“…The important features of employed methods and their individual merits have been reviewed extensively in 2012 [22]. Concomitant with analysis techniques, MS data analysis software has matured in the last years [23], now offering robust, label-free quantification and multiplexing of up to 10 samples [24] in one MS run. Since 2012, some of these technological advances have been implemented, yet traditional methods have remained popular in Brucella proteomics.…”
Section: Proteomics Technologies and Their Use For Brucellamentioning
confidence: 99%
“…A very interesting example for NHS esters is the isobaric tag for relative and absolute quantification (iTRAQ) reagents. These reagents are used mainly in the field of proteomics and a very recent review has reported about the current trends in their design and development (Bąchor et al, ). However, these reagents are also used for the labeling of amino acids.…”
Section: Isotope‐coded Derivatization Reagents For Lc–ms Analysismentioning
confidence: 99%
“…Other applications such as environmental and food analysis were briefly summarized as some of the used ICD reagents in these fields were further used for analyzing biological specimens or have a strong potential to be used in the biomedical field. Regarding ICD for proteomics, many summarizing reviews for this topic have been published very recently (Bąchor, Waliczek, Stefanowicz, & Szewczuk, 2019;Hoedt, Zhang, & Neubert, 2019;Liu et al, 2019;Pappireddi, Martin, & Wühr, 2019;Patole & Bindschedler, 2019), and so they will not be covered in this article.…”
Section: Isotope-coded Derivatization Reagents For Lc-ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The 2,4,6-triphenylpyridinium-modified peptides generate an abundant protonated 2,4,6-triphenylpyridinium ion in MS/MS experiments. This fragment was found to be a promising reporter ion for the multiple reactions monitoring (MRM) analysis [16].…”
Section: Introductionmentioning
confidence: 99%